Investigating the Resiliency of the Framing Effect in Information Visualization - Maroco, A.; Gonçalves, Daniel; Gama, Sandra; Alves, T. (2025 International Conference on Graphics and Interaction (ICGI), 2025)
When individuals conduct complex cognitive thinking under uncertainty, their judgments and decisions may rely on individual unconscious approximations and rules of thumb. These may lead to systematic deviations from rational thinking called cognitive biases. Recent research in the information visualization field has tackled how these rationale limitations affect visualization-supported decision-making. However, there is such a small body of evidence that it offers little guidance to practitioners. The present study explores the framing effect in an information visualization context by depicting a decision-making problem regarding a hypothetical disease with visual encodings. We conducted user tests (N=91) where we collected user interaction metrics and the decision-making process between a set of options under different framing contexts. Our findings suggest that bar charts with error bars help mitigate the framing effect for most of the experiment sample. Developing cognitive bias-aware decision support systems is of utmost importance to leverage the full potential of information visualization and make it widely available to jobs where visualization-supported decisions are critical.